Overcoming Uncertainty when WhatsApp Errors/Downs: Convergence of Interpersonal Communication and Mass Communication - Robby Adwa Fahlepi; Andre Noevi Rahmanto; Sri Hastjarjo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of WhatsApp is a manifestation of the development of digital communication. Based on data from the 2021 Indonesian Digital Literacy Status Survey, 93.6% of respondents used the WhatsApp application to share, disseminate and forward information on social media. This research aims to describe the phenomenon as an impact of WhatsApp Error/Down so that it can be used as a reference for behavior. The WhatsApp Error/Down phenomenon creates uncertainty for its users. Looking from the communication side, Uncertainty Reduction Theory is used to overcome this uncertainty. The research used a qualitative approach where researchers conducted interviews and sent questionnaires to informants (WhatsApp users). Literature studies are complementary in answering this uncertainty. Researchers also see the convergence between interpersonal communication and mass communication in this digital era. Based on the research results, it was found that the majority of users use interactive methods to overcome this phenomenon. WhatsApp users tend to use other media to overcome the ongoing WhatsApp Error/Down phenomenon, such as using Telegram, Instagram and Line